Emergency endoscopic variceal ligation following variceal rupture in patients with advanced hepatocellular carcinoma and portal vein tumor thrombosis: a retrospective study. Issue 1 (December 2016) - Kawai, Toshihiro; Yashima, Yoko; Sugimoto, Takafumi; Sato, Takahisa; Kanda, Miho; Enomoto, Nobuyuki; Sato, Shinpei; Obi, Shuntaro
Abstract Background The outcomes of treatment of ruptured varices in patients with hepatocellular carcinoma (HCC) and portal vein tumor thrombus (PVTT) are unclear. We therefore evaluated the long- (rebleeding and death) and short-term (immediate death within 24 h of variceal bleeding diagnosis) outcomes of patients with PVTT who underwent emergency variceal band ligation. Methods Data on 62 patients with PVTT and endoscopically proven esophageal or gastric variceal bleeding from 2007 to 2012 were studied. In most cases, the varices were treated using endoscopic variceal band ligation (EVL). We assessed the patients' rebleeding-free and overall survival using the Kaplan-Meier method, and a Cox proportional hazard model was used to analyze effect of independent factors on rebleeding-free and overall survival times. Results Most patients had decompensated cirrhosis and were classified as Child-Pugh class B (56 %) or C (36 %). A total of 35 patients (56 %) had PVTT in the main portal trunk. Among all patients, 58 (94 %) and 4 (6 %) had esophageal and gastric variceal bleeding, respectively. Bleeding was managed using EVL in all, but one patient (98 %) who was treated with a Sengstaken-Blakemore tube. A total of 24 patients (39.3 %) experienced rebleeding, and these patients had a median overall survival time of 36 days. A PVTT in the main portal trunk was predictive of rebleeding (hazard ratio 3.706, p  = .0223), and α-fetoprotein-L3 levels <37.4 % (hazard ratio 0.464, p  = 0.015) and Child-Pugh class A/B (hazard ratio 0.398, p  = 0.007) were associated with overall survival. We observed 95 bleeding events in 62 patients. EVL achieved hemostasis in 92 of the 95 bleeding events, whereas seven immediate deaths occurred due to variceal bleeding (7/92, 7.6 %). All three bleeding events treated with modalities other than EVL resulted in immediate deaths. Conclusions EVL is a safe and effective treatment of variceal ruptures in patients with HCC and PVTT. After successful hemostasis, alleviation of the underlying liver function impairment and tumor control are equally important for a good prognosis.